Photothermal technique-enabled ambient production of microalgae biodiesel: Mechanism and life cycle assessment. (February 2023) - Huang, Jinshu; Wang, Junqi; Huang, Zhuochun; Liu, Tengyu; Li, Hu
Graphical abstract: Highlights: A new biomass-based graphene-like photothermal catalyst S-NGL-600 was simply prepared. Response surface methodology optimized microalgae biodiesel production (96.8 % yield) Infrared thermal imaging indicated formation of a local photothermal catalytic system. Light-to-heat favored removal of in situ formed water to enable biodiesel synthesis. LCA showed superior eco-friendliness of light-enhanced microalgae-to-biofuel process. Abstract: Thermocatalytic (trans)esterification of oils/lipids to produce biodiesel is generally energy-consuming, reversible, and controlled by the equilibrium law. Herein, a light-induced photothermal process was illustrated to be highly efficient for biodiesel production (96.8 % yield) from microalgae lipids at room temperature enabled by a biomass-based SO3 H-functionalized graphene-like heterogeneous catalyst (S-NGL-600), as optimized by response surface methodology. Infrared thermal imaging indicated that interfacial solar heating led to forming a local photothermal catalytic system, reaching 72.2 °C in 2 min. The local light heating was conducive to evaporation and removal of water from acid sites, resulting in local excess of microalgae lipids to facilitate the forward reaction. Notably, the photothermal catalyst was highly recyclable and exhibited a significantly higher conversion rate of microalgae lipids than industrially used catalyst H2 SO4 . Life cycle assessment suggested energy-saving advantage (0.87 MJ/MJ) and environmental protection (-89.42 CO2eq /MJ) of the photothermal-driven protocol for microalgae biodiesel production.